هل يمكن توحيد سوق الصرف الرسمي و الموازي للدينار الجزائري ؟: Is it possible to unify the official and parallel exchange market for the Algerian dinar? - قنيش محمد; زايري بلقاسم (Journal of North African Economies, 2025)
The aim of our research is to explore the short- and long-term relationship between the official and unofficial market’s exchange rate (euro/Algerian dinar). In order to analyse this relationship, we use monthly data of official and parallel exchange rates for the Algerian dinar covering the period from 2010 to 2019. Our econometric results indicate that the two rates are cointegrated, implying a long-term relationship between them. Hence, we find that the official exchange rate undertakes the adjustment to the long -run equilibrium. Granger’s causality test shows a bilateral relationship in the long run between the two rates. These results show that the devaluation of the Algerian dinar cannot be used as a unique way to unify the two exchange markets.